2014
DOI: 10.1007/s12149-013-0798-1
|View full text |Cite
|
Sign up to set email alerts
|

Age-related decline in dopamine transporter in human brain using PET with a new radioligand [18F]FE-PE2I

Abstract: [(18)F]FE-PE2I allowed reliable quantification of DAT, not only in the caudate and putamen but also in the substantia nigra. From the results, we demonstrated the age-related decline in the caudate and putamen as reported in previous studies, and additionally for those in the substantia nigra for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 40 publications
4
33
0
Order By: Relevance
“…Imaging studies have revealed gradual and region-specific reductions in DAT density with age (Shingai et al, 2014; Volkow et al, 1998, 1996), supporting post-mortem findings of significant loss of nigrostriatal DA neurons even in the absence of neurodegenerative disease (Fearnley and Lees, 1991). Additionally, several major age-dependent disorders are known to be associated with DAT polymorphisms, such as Alzheimer’s disease (Lin et al, 2012) and Parkinson’s disease (le Couteur et al, 1997; Ritz et al, 2009).…”
Section: Introductionmentioning
confidence: 54%
“…Imaging studies have revealed gradual and region-specific reductions in DAT density with age (Shingai et al, 2014; Volkow et al, 1998, 1996), supporting post-mortem findings of significant loss of nigrostriatal DA neurons even in the absence of neurodegenerative disease (Fearnley and Lees, 1991). Additionally, several major age-dependent disorders are known to be associated with DAT polymorphisms, such as Alzheimer’s disease (Lin et al, 2012) and Parkinson’s disease (le Couteur et al, 1997; Ritz et al, 2009).…”
Section: Introductionmentioning
confidence: 54%
“…The dopamine transporter (DAT) is a presynaptic protein with a key role in dopamine neurotransmission and is a sensitive marker of the dopaminergic neuronal integrity [10]. Available striatal DAT sites diminish in the course of PD [11], and age is proposed to have a slight and uneven effect on it, as compared to the physiological decline that occurs with aging [12,13]. In vivo imaging of the DAT with SPECT [14] has become available in an increasing number of movement disorders clinics.…”
Section: I-fp-cit Spect Imaging Data Analysismentioning
confidence: 99%
“…Imaging studies in controls propose that there is a physiological decline of the striatal DAT expression that is age-related [26] and that this decline is even for the caudate and the putamen [13]. In PD, studies suggest that striatal DAT availabilities decline to a greater extent than in controls Representative images (on the axial plane) of 123 I-FP-CIT specific to non-specific binding in the striatum of two Parkinson's disease (PD) patients at baseline (upper row) and at follow-up (lower row).…”
Section: S9mentioning
confidence: 99%
“…12,13 The overdosing effect of dopaminergic drugs may be more severe in patients with younger PD onset, considering that dopaminergic function physiologically declines with aging. 14 Dopaminergic drugs interfere with phasic processing of rewards provided by ventral striatum dopamine neurons, strengthening dopaminergic peaks (associated with unexpected rewards), and preventing dopaminergic dips (associated with failures of expected rewards), as confirmed by impairments in reward learning induced by dopaminergic therapy in the early stages of PD; 15,16 this effect is stronger for the tonic stimulation provided by dopamine agonists in comparison with the phasic stimulation provided by levodopa. 17,18 The alteration of reward learning (strengthened dopaminergic peaks associated with rewards, prevented dopaminergic dips associated with failures of expected rewards) induced especially by dopamine agonists represents the pathophysiological basis 19,20 of behavioral addictions in PD patients.…”
Section: Introductionmentioning
confidence: 99%